Radiological and functional outcome of conservatively managed middle one third clavicle fractures - Mohan M. Desai; Shere, Pranav P.; Chopade, Ranjit; Shahare, Pratik Y. (International Journal of Research in Orthopaedics, 2023)
Background: We aim to assess radiological and functional outcome of conservatively managed middle one third clavicle fractures in Indian population. Clavicle fractures represent 2% to 10% of all fractures. In middle third clavicle fractures, conservative management is the commonest approach. In uncomplicated non displaced midshaft fractures, patients treated non operatively with these conservative measures have fewer complications and a timely recovery as those treated operatively. Conservative management is a simpler yet effective mode of management in middle one third clavicle fractures. Methods: Patients managed conservatively for clavicle fractures were assessed on OPD basis with follow up chest X-ray with bilateral shoulder AP view for radiological signs of union and assessing percent shortening and two questionnaires. Constant shoulder score which assess pain, degree of function, range of motion and muscular force and, simple shoulder test, self administered questionnaire defining one or more affirmative answers to find the satisfaction after treatment modality which were tabulated in Microsoft excel sheets. Results: Out of the 55 patients enrolled in the study 52 showed signs of union at 6 months follow up with mean fracture union time of 13.9 weeks. At 6 months follow up Mean Constant Shoulder score was 87.1 with excellent outcome in 67.67 percent patients and using Simple Shoulder Test satisfaction rate was found to be 78.18 percent. Conclusions: Solid evidence in favour of non-operative treatment for fractures with remaining contact of the bone fragments. Non-surgical management of middle third clavicle fractures yield excellent results. Clear indications for conservative treatment versus surgical fixation of displaced midshaft fractures have not finally been established yet. We recommend conservative management for uncomplicated middle one third clavicle fractures.